Tools for Adjusting Research Methods and Techniques to Research Processes - Dzwigol, Н. (Економічний вісник Донбасу, 2020)
The aim of the following paper is to present the tools for adjusting research methods and techniques to research processes, developed by the author hereof. In order to evaluate and select individual research methods and techniques, a group evaluation of experts was employed in the paper. The developed tool consists of five phases that allow to answer any question which a researcher (academic and practitioner) should pose to himself/herself. What is more, the application of the tool eliminates a need to diagnose research methods and techniques available in the literature, through the use of a classification pattern which corresponds to five components of the procedure phases. У статті представлено розроблені автором інструменти для адаптації методів та технік у дослідницьких процесах. Для оцінки та відбору окремих методів та прийомів дослідження в роботі було залучено групову оцінку експертів. Розроблений інструментарій складається з п'яти фаз, що дозволяють відповісти на будь-яке питання, яке дослідник (вчений та практик) повинен поставити перед собою. Більше того, застосування інструментарію позбавляє потреби діагностувати доступні в літературі методи та прийоми дослідження, використовуючи шаблон класифікації, який відповідає п’яти компонентам етапів процедури. В статье представлены разработанные автором инструменты для адаптации методов и техник в исследовательских процессах. Для оценки и отбора отдельных методов и приемов исследования в работе была использована групповая оценка экспертов. Разработанный инструментарий состоит из пяти фаз, позволяющих ответить на любой вопрос, который исследователь (ученый и практик) должен поставить перед собой. Более того, применение инструментария исключает необходимость диагностировать доступные в литературе методы и приемы исследования, используя шаблон классификации, который соответствует пяти компонентам этапов процедуры.